Authenticated-encryption with associated-data - Rogaway P. (2014)
When a message is transformed into a ciphertext in a way designed to protect both its privacy and authenticity, there may be additional information, such as a packet header, that travels alongside the ciphertext (at least conceptually) and must get authenticated with it. We formalize and investigate this authenticated-encryption with associated-data (AEAD) problem. Though the problem has long been addressed in cryptographic practice, it was never provided a definition or even a name. We do this, and go on to look at efficient solutions for AEAD, both in general and for the authenticated-encryption scheme OCB. For the general setting we study two simple ways to turn an authenticated-encryption scheme that does not support associated-data into one that does: nonce stealing and ciphertext translation. For the case of OCB we construct an AEAD-scheme by combining OCB and the pseudorandom function PMAC, using the same key for both algorithms. We prove that, despite "interaction" between the two schemes when using a common key, the combination is sound. We also consider achieving AEAD by the generic composition of a nonce-based, privacy-only encryption scheme and a pseudorandom function.